Sistem Pendukung Keputusan Penerimaan Bantuan Program Keluarga Harapan (Pkh) Dengan Menggunakan Metode Simple Additive Weighting (Saw) Berbasis Web - Galih Wangsa Putra; Budi Apriyanto (CV. Multi Kreasi Media, 2022)
Poverty is still a problem in Indonesia and is a national concern and appropriate treatment. In 2007, the government created a program intended for a family called the Program Keluarga Harapan (PKH) with the aim of breaking the chain of poverty, changing unsupportive actions, as well as the welfare and quality of human resources. Unfortunately, the support system for receiving PKH assistance deals with problems regarding potential recipients of PKH assistance, where data management is still conventional and does not match the predetermined criteria, so that the assistance is not yet on target. As a solution to these problems, the authors developed a decision support system using the Simple Additive Weighting (SAW) method which is often known as the weighted summation, where the Simple Additive Weighting (SAW) method has the advantage of determining attribute values, then it will be continued by determining a chaining process. which will select the best from various alternatives, and the assessment will be more precise because it is based on predetermined criteria and preference weights. The result of this research is a decision support system application that gives output in the form of ranking of 126 poor family data which has very good accuracy of 0.4800. So that it gets the priority that receives the most PKH assistance to meet the limited PKH quota in accordance with the criteria that have been determined by the government so that the assistance is right on target.